Sejarah & sosioekonomi wanita Melayu Kedah, 1881-1940 - Mahani Musa , 1964- (Penerbit Universiti Kebangsaan Malaysia, 2005)
Malay women from Kedah in history and their role in cultural, and socioeconomic aspects of Malaysia, 1881-1940